Relationships between photochemical reflectance index and light-use efficiency in deciduous and evergreen broadleaf forests (Remote Sensing of Environment, 2014)
In this study, we evaluate the relationships between the photochemical reflectance index (PRI) and light-use efficiency (LUE) based on eight years of continuous in situ measurements acquired on a half-hourly basis for PRI, NDVI (Normalized Difference Vegetation Index), the main micrometeorological variables and net CO2 exchange data in two deciduous and evergreen mature forests. More specifically, the objectives of this study include investigating the daily, seasonal, and interannual variations of PRI and LUE; linking PRI variations to the main influencing meteorological and eco-physiological variables; and evaluating the performance of PRI as a remote-sensing proxy of LUE under different environmental conditions. The data analysis was performed at different time scales within the season using moving temporal windows and between years. On a seasonal scale, statistical analyses revealed positive relationships between PRI and absorbed photosynthetically active radiation (aPAR) and negative relationships between PRI and LUE. Over shorter periods of a few days, the signs of these relationships remained unchanged; however, their correlations were strongly improved. The highest correlations were most often observed over periods characterized by clear or slightly overcast skies. However, all the periods of clear skies did not involve improvements in the relations of PRI vs. aPAR or PRI vs. LUE. Temporal variations of the intercept (called PRI0 in this study) of PRI vs. aPAR regressions suggest the presence of a temporal trend that may reflect seasonal changes of the biochemical characteristics of the canopy. Regardless of the cause of this trend, it is important to note that once PRI0 was subtracted from the measured PRI, the correlations between the corrected PRI and LUE for each year were significantly improved, and a stable multi-year model was obtained. Nevertheless, further studies are required to explain the temporal changes of PRI0 during the season and to develop a more accurate disentangling approach that would make PRI-based remote-sensing of ecosystem light-use efficiency less sensitive to confounding factors related to spatial and temporal changes in the structural and biochemical properties of the canopy.

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.
The following values have no corresponding Zotero field: accession-num: 22159896

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought. (Oecologia, 2012)
Mediterranean trees must adjust their canopy leaf area to the unpredictable timing and severity of summer drought. The impact of increased drought on the canopy dynamics of the evergreen Quercus ilex was studied by measuring shoot growth, leaf production, litterfall, leafing phenology and leaf demography in a mature forest stand submitted to partial throughfall exclusion for 7 years. The leaf area index rapidly declined in the throughfall-exclusion plot and was 19% lower than in the control plot after 7 years of treatment. Consequently, leaf litterfall was significantly lower in the dry treatment. Such a decline in leaf area occurred through a change in branch allometry with a decreased number of ramifications produced and a reduction of the leaf area supported per unit sapwood area of the shoot (LA/SA). The leafing phenology was slightly delayed and the median leaf life span was slightly longer in the dry treatment. The canopy dynamics in both treatments were driven by water availability with a 1-year lag: leaf shedding and production were reduced following dry years; in contrast, leaf turnover was increased following wet years. The drought-induced decrease in leaf area, resulting from both plasticity in shoot development and slower leaf turnover, appeared to be a hydraulic adjustment to limit canopy transpiration and maintain leaf-specific hydraulic conductivity under drier conditions.

Ectomycorrhizal communities in a Mediterranean forest ecosystem dominated by Quercus ilex: seasonal dynamics and response to drought in the surface organic horizon - Richard, Franck; Roy, Melanie; Shahin, Oula; Sthultz, Christopher; Duchemin, Myriam; Joffre, Richard; Selosse, Marc-André (Annals of Forest Science, 2011)
• Introduction Millions of hectares of Quercus ilex forests dominate disturbed landscapes in the western part of the Mediterranean basin. Although these forests are very widespread, little is known about the composition and structure of their associated ectomycorrhizal fungal communities. • Results and discussion We examined seasonal patterns in ectomycorrhizal communities and their response to increased drought using a rainfall exclusion experiment established in a Q. ilex coppice since 2003. Ectomycorrhizae were sampled four times in 2007–2009. By sequencing fungal ITS, we identified 129 species in 1,147 sequenced ectomycorrhizal root tips. The fungal community in the surface organic horizon was well described by the logseries theoretical model, with 47.9% of singleton species. The composition of the community was strongly dominated by Basidiomycetes, with three families (Thelephoraceae, Russulaceae and Cortinariaceae) accounting for 72.9% of the root tips. Relative abundance of Russulaceae and Thelephoraceae showed pronounced seasonal shifts. Experimental reduction of rainfall resulted in significant shifts in community composition and seasonal fluctuations but had no effect on global richness of the community. • Conclusions Together, these results suggest that the predicted rainfall reduction in this region due to climate change will lead to shifts
Keywords: Drought; ectomycorrhizal communities; Global change; Mediterranean forests

Leaf CO2 efflux is attenuated by acclimation of respiration to heat and drought in a Mediterranean tree (Functional Ecology, 2011)
* 1Understanding the effect of water deficit on plant respiration and its temperature sensitivity at long time-scales is important for anticipating the shift in ecosystem dynamics that is expected to occur as a result of climate change. * 2We investigated seasonal variations of leaf dark respiration and sensitivity to temperature in the upper and lower canopy of Quercus ilex trees in a forest stand that had been exposed to either 33% throughfall reduction or normal rainfall for the preceding 6 years. * 3For upper and lower canopy leaves, light-saturated photosynthesis and respiration at a reference temperature of 15 °C (R15) had the lowest values in late summer, when both traits were lower in trees subjected to throughfall reduction than in those subject to control conditions. Respiration acclimated to seasonal shifts in temperature, more intensively through summer than winter and in throughfall-exclusion than control trees. Foliar concentration of soluble sugars was positively correlated with R15 across seasons. * 4As leaf respiration decreased with increasing water deficit, and the relationship between water status and respiration did not differ between trees that had been exposed to 7 years of enhanced drought when compared with controls, we suggest that drier conditions projected for the Mediterranean may attenuate the stimulation of leaf respiratory CO2 release by global warming in Q. ilex forests.

Is selective thinning an adequate practice for adapting Quercus ilex coppices to climate change? - Rodriguez-Calcerrada, Jesus; Pérez-Ramos, Ignacio M.; OURCIVAL, JEAN-MARC; Limousin, Jean-Marc; Joffre, Richard; Rambal, Serge (Annals of Forest Science, 2011)
& Introduction Future climatic scenarios demand an increasing involvement of management for forest preservation, but little is known on how forestry practices will benefit stands in facing variation of climatic components. & Objectives We investigated how selective thinning affected the response of an old Quercus ilex coppice to 6 years of throughfall reduction. Plots thinned from below (≈30% basal area removal) and unthinned plots were subject to either throughfall exclusion (TE; ≈33% throughfall reduction) or normal rainfall. Stem diameter growth, stem survival, and seed and sprout production were measured. & Results TE did not have a significant effect on stem growth but it reduced the production of viable acorns. Also, in the absence of thinning, TE accelerated the mortality of small stems and stimulated the emergence of new sprouts. Thinning reduced stem mortality, enhanced growth of residual stems, and caused a profuse emission of resprouts. Thinning also increased total seed production, but the crop had a large proportion of aborted seeds, especially in those areas subject to TE. & Conclusion The mere elimination of suppressed and diseased stems in abandoned Q. ilex coppice stands helps remaining trees to cope with current and future (probably longer and more intense) droughts. Potentially drier conditions might attenuate the success of thinning in producing a viable seed crop.
Keywords: Drought; forest adaptation strategy; seed production; sprouting; stem growth

Modelling rainfall interception in a mediterranean Quercus ilex ecosystem: Lesson from a throughfall exclusion experiment (Journal of Hydrology, 2008)
In the Mediterranean basin, precipitation is expected to decline by the end of the 21st century as a consequence of climate change. A throughfall exclusion experiment has been established in a Quercus ilex coppice in southern France to anticipate the response of this ecosystem to a reduced precipitation amount by removing part of the throughfall. The experiment involved four 140 m 2 plots: a control plot, a throughfall exclusion plot, a thinned plot and a throughfall exclusion in a thinned plot. This experiment has been used during nearly two years to monitor throughfall amounts in the different plots. Additionally, stemﬂow has been recorded on 20 trees between 25 April 2006 and 15 May 2007. The control plot had a stem density of 6885 stems ha 1 and a leaf area index of 3.1, rainfall partitioning into interception loss, throughfall and stemﬂow was, respectively, 30.9%, 56.6% and 12.5% of the total precipitation (1605 mm over the study period). Thinning reduced the stem basal area by 33% and the total interception loss by 34.6%. Given the rainfall partitioning, the throughfall exclusion was found to remove 19% of total precipitation, which was conﬁrmed by soil water content measurements. The revised Gash analytical model predicted interception with an agreement of 6.2% of total precipitation. Results show a good transferability of the model to a plot with a different stem density, thus supporting the idea that model parameters and evaporation from a wet canopy scale linearly with canopy cover.

Photosynthesis, growth and structural characteristics of holm oak resprouts originated from plants grown under elevated CO2 - Aranda, Xavier; Agustí, Cristina; Joffre, Richard; Fleck, Isabel (Physiologia Plantarum, 2006)
The physiological characteristics of holm oak (Quercus ilex L.) resprouts originated from plants grown under current CO2 concentration (350 μl l−1) (A-resprouts) were compared with those of resprouts originated from plants grown under elevated CO2 (750 μl l−1) (E-resprouts). At their respective CO2 growth concentration, no differences were observed in photosynthesis and chlorophyll fluorescence parameters between the two kinds of resprout. E-resprouts appeared earlier and showed lower stomatal conductance, higher water-use efficiency and increased growth (higher leaf, stem and root biomass and increased height). Analyses of leaf chemical composition showed the effect of elevated [CO2] on structural polysaccharide (higher cellulose content), but no accumulation of total non-structural carbohydrate on area or dry weight basis was seen. Four months after appearance, downregulation of photosynthesis and electron transport components was observed in E-resprouts: lower photosynthetic capacity, photosystem II quantum efficiency, photochemical quenching of fluorescence and relative electron transport rate. Reduction in ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) activity, deduced from the maximum carboxylation velocity of RuBisCo, accounts for the observed acclimation. Increased susceptibility of photosynthetic apparatus to increasing irradiance was detected in E-resprouts.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: CO2; Elevated CO2; Fluorescence (voyant); Growth; photosynthesis; Resprouts

Photosynthesis, growth and structural characteristics of holm oak resprouts originated from plants grown under elevated CO2 (Physiologia Plantarum, 2006)
The physiological characteristics of holm oak (Quercus ilex L.) resprouts originated from plants grown under current CO2 concentration (350 μl l−1) (A-resprouts) were compared with those of resprouts originated from plants grown under elevated CO2 (750 μl l−1) (E-resprouts). At their respective CO2 growth concentration, no differences were observed in photosynthesis and chlorophyll fluorescence parameters between the two kinds of resprout. E-resprouts appeared earlier and showed lower stomatal conductance, higher water-use efficiency and increased growth (higher leaf, stem and root biomass and increased height). Analyses of leaf chemical composition showed the effect of elevated [CO2] on structural polysaccharide (higher cellulose content), but no accumulation of total non-structural carbohydrate on area or dry weight basis was seen. Four months after appearance, downregulation of photosynthesis and electron transport components was observed in E-resprouts: lower photosynthetic capacity, photosystem II quantum efficiency, photochemical quenching of fluorescence and relative electron transport rate. Reduction in ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) activity, deduced from the maximum carboxylation velocity of RuBisCo, accounts for the observed acclimation. Increased susceptibility of photosynthetic apparatus to increasing irradiance was detected in E-resprouts.

Isoprenoid emissions of Quercus spp. (Q. suber and Q. ilex) in mixed stands contrasting in interspecific genetic introgression (New Phytologist, 2004)
• Among oak species, Quercus ilex is classiﬁed as a monoterpene emitter and Q. suber is mainly known as a nonisoprenoid emitter. The extent and origin of this diversiﬁcation is unknown. • We examined intra- and interspeciﬁc emission variability in two mixed stands which differed in their level of hybridization and reciprocal genetic introgression based on variations in cytoplasmic (chloroplast DNA) and nuclear (allozyme) markers. • At both sites all trees identiﬁed as Q. ilex, or as recent descendants from Q. ilex × Q. suber hybrids, emitted monoterpenes. Of Q. suber trees (genetically introgressed or not by Q. ilex), 91% were also monoterpene emitters, and the remainder nonemitters. One tree identiﬁed as a Q. canariensis × Q. ilex hybrid emitted both isoprene and monoterpenes. Compared with Q. ilex, the standard emission rate of Q. suber was higher in summer and lower in autumn. Both species emitted the same monoterpenes, proportions of which showed signiﬁcant intra- and interspeciﬁc variability. • The results suggest that Q. suber populations in the French Mediterranean intrinsically emit monoterpenes, and that gene ﬂow between oak species contributes to diversiﬁcation of emission signatures.

Isoprenoid emissions of Quercus spp. (Q. suber and Q. ilex) in mixed stands contrasting in interspecific genetic introgression - Staudt, Michael; Mir, Celine; Joffre, Richard; Rambal, Serge; Bonin, Aurelie; Landais, Damien; Lumaret, Roselyne (New Phytologist, 2004)
• Among oak species, Quercus ilex is classiﬁed as a monoterpene emitter and Q. suber is mainly known as a nonisoprenoid emitter. The extent and origin of this diversiﬁcation is unknown. • We examined intra- and interspeciﬁc emission variability in two mixed stands which differed in their level of hybridization and reciprocal genetic introgression based on variations in cytoplasmic (chloroplast DNA) and nuclear (allozyme) markers. • At both sites all trees identiﬁed as Q. ilex, or as recent descendants from Q. ilex × Q. suber hybrids, emitted monoterpenes. Of Q. suber trees (genetically introgressed or not by Q. ilex), 91% were also monoterpene emitters, and the remainder nonemitters. One tree identiﬁed as a Q. canariensis × Q. ilex hybrid emitted both isoprene and monoterpenes. Compared with Q. ilex, the standard emission rate of Q. suber was higher in summer and lower in autumn. Both species emitted the same monoterpenes, proportions of which showed signiﬁcant intra- and interspeciﬁc variability. • The results suggest that Q. suber populations in the French Mediterranean intrinsically emit monoterpenes, and that gene ﬂow between oak species contributes to diversiﬁcation of emission signatures.
Keywords: basal emission rate; chemotaxonomy; chemotypes; Evergreen oaks; genetic introgression; isoprene; Monoterpenes; VOC (volatile organic compound) emissions.

The key-role of topsoil moisture on CO$_2$ efflux from a Mediterranean Quercus ilex forest (Ann. For. Sci., 2003)
CO2 respiratory losses partly determine net carbon ecosystem exchanges. The main objective of this paper was to understand regulation imposed by soil water content and temperature on soil and ecosystem CO2 efflux in a holm oak (Quercus ilex L.) Mediterranean forest. Soil CO2 efflux was monitored monthly during 1999 and 2001. Moreover, experimental water treatments were conducted in 1999 over 9 small plots (0.3 m2) during nine months. Results showed strong decreases of soil CO2 efflux for a relative soil water content below 0.7. Ecosystem respiration measured by eddy covariance over a 4-year period showed strong sensitivity to soil water content and temperature. Severe limitations of soil and ecosystem efflux imposed by low values of soil water content occurred on about 90 days per year. The best adjustments of soil and ecosystem CO2 efflux were obtained using regression models where the exponential effect of temperature is linearly related to soil water content ( r2 = 0.68 and 0.79 for soil and ecosystem respectively). Our results highlighted strong differences in respiration sensitivity to topsoil moisture between soil and ecosystem. When the relative water content (RWC) is low (0.4), an increase of 1 °C provokes an increase of soil respiration of 5.7% and an increase of ecosystem respiration of 8.6%. For nonlimiting soil water conditions, at RWC = 1, the increases of respiration caused by a 1 °C temperature increase are of 8.5% and 16.5% for soil and ecosystem respectively. These results emphasized the probable determinant influences of changes in soil water regime for respiratory fluxes and net carbon exchanges of Mediterranean forest ecosystems.

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.9

Internal remobilization of carbohydrates, lipids, nitrogen and phosphorus in the Mediterranean evergreen oak Quercus ilex - Cherbuy, Bénédicte; Joffre, Richard; Gillon, Dominique; Rambal, Serge (Tree Physiology, 2001)
Remobilization of internal resources is an important mechanism enabling plants to be partly independent of external nutrient availability. We assessed resource remobilization during the growing period in woody and foliar tissues of leafy branches of mature evergreen Mediterranean oak (Quercus ilex L.) at three field sites. We compared nonstructural carbohydrates, lipids, nitrogen and phosphorus pools in leaves and stems before bud burst (March) and at the end of the growing period (July). We also experimentally defoliated leafy branches to determine the storage function of old leaves. Changes in pools of carbon compounds in leaves and stems during spring and in response to defoliation indicated that foliar and woody tissues could provide carbon to support shoot growth. Independently of stem age, soluble sugar and lipid pools decreased significantly during spring. Changes in leaf pools between March and July involved all compounds measured except starch and were accompanied by a 5%; decrease in mean leaf biomass. During the same period, 15%; of the nitrogen and 25%; of the phosphorus were removed from leaves. In contrast, woody tissues did not remobilize nitrogen or phosphorus. Our results support earlier hypotheses that leaves of evergreen species have a primary role in resource remobilization.
10.1093/treephys/21.1.910.1093/treephys/21.1.9
Keywords: defoliation; Growth; nutrient storage; resource remobilization

Within-tree variation in transpiration in isolated evergreen oak trees: evidence in support of the pipe model theory (Tree Physiology, 2001)
Within-tree variation in sap flow density (SFD) was measured in two isolated evergreen oak (Quercus ilex L.) trees growing in an oak savannah (dehesa) in southwest Spain. Sap flow was estimated by the constant heating method. Three sensors were installed in the trunk of each tree in three orientations: northeast (NE), northwest (NW) and south (S). Sap flow density was monitored continuously from May 18 to September 27, 1993. Daily values of SFD ranged between 500 and 4500 mm3 mm−2 day−1. There were significant differences in SFD between orientations; SFD was higher in the NE and NW orientations than in the S orientation. These differences were noted on both a daily and seasonal time scale, and were less pronounced on cloudy days and at the end of the drought period, when SFD was relatively low. Our results support the idea that branches of trees can be viewed as a collection of small independent plants.
10.1093/treephys/21.6.409

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise - Filho Teixeira, José; Damesin, Claire; Rambal, Serge; Joffre, Richard (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements
Keywords: Arbutus unedo; mixed Mediterranean woodland; Penman-Monteith equation; Quercus ilex; Quercus pubescens; sap flow; stomatal and canopy conductances

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements

Changes in litter during the initial leaching phase: an experiment on the leaf litter of Mediterranean species (Soil biology and biochemistry, 1995)
A laboratory experiment was carried out with the litter of 7 Mediterranean species of plants to compare their mass losses during the initial leaching phase of decomposition. To this end, the leaf and needle litter of deciduous, marcescent (deciduous species in which the withered leaves remain on the tree. for several months) and evergreen broad-leaved species and pine was immersed for 10 days in demineralized water, in the dark at 22°C. Samples were taken at 1,6, 24,72, 168 and 240 h. Depending on the species, the litter lost between ‘T-15% of initial dry mass, and water content values were between 130-360% of dry mass. The water absorption rate was positively correlated with the initial cellulose content of the litter and negatively correlated wil:h the initial leaf density, but the water content at the end of the experiment, the leaching rate and the total mass loss were uncorrelated with any of the initial litter characteristics studied. For 100 g of litter at the start (as dry matter), the losses after 240 h of immersion in water were, when they were significant, 5-8 g of C, 70-l 30 mg of N (significant for 3 species), 4-40 mg of soluble sugars and 3 g of inorganic elements (significant for only 2 species). In contrast, the quantities of lignin and cellulose in the litter remained unchanged. Most of the leaching losses (SCrSO%) therefore consisted of C. During leaching, the litter showed a tendency to become more concentrated in cellulose and lignin and poorer in sugars. Pine needle litter was distinguished by its low water absorption and low mass loss during leaching. In general, the litters of deciduous species were more absorbent than the litters of evergreen species. In contrast, the losses of water-soluble substances were not significantly different between these 2 groups of litters. In the broad-leaved species, the losses of water-soluble substances were slower and 2-3 times lower, compared to results already published for species from mesic biomes

Caractérisation de formations végétales mediterranéennes à partir de données ‘Thematic Mapper’ Une étude de cas en Andalousie (Espagne) (International Journal of Remote Sensing, 1987)
Abstract The study is focused on the characterization of vegetation formations in a Mediterranean area (943 km2) located in southern Spain: herbaceous canopies (rangelands), shrubby vegetation (?matorral?) and complex woody/herbaceous formations (?dehesa?). Vegetation formations (physiognomical units) have been characterized by their spectral responses in the six reflective TM channels and by vegetation indices. From the ratio index TM4/TM3 there has been derived a map displaying seven classes (water, bare soil and five biomass levels reflecting the hierarchy of vegetation formations). Channels TM3, TM4 and TM5 have been considered for a supervised classification into nine land-cover categories (seven vegetation formations, bare soil and water). The proportion of correct classification of vegetation formations is about 78 per cent when considering test areas. Classification made from three principal components gives similar results.
doi: 10.1080/01431168708954777